Lentinus tigrinus, an addition to newly recorded and successfully propagated wild strain of Philippine edible mushroom - Dulay, Rich Milton R.; Cabrera, Esperanza C.; Kalaw, Sofronio P.; Reyes, Renato G.; Eguchi, Fumio (2011)
Most of the commercially cultivated mushrooms in the Philippines were imported from other countries and their cultivation technologies were modified to suit the local conditions. Though well accepted by most Filipinos, these imported strains are not always available in the local market and one of the strategies is to use our own mycological resources. In the past, we were successful in the domestication of Collybia, Schizophyllum, Ganoderma, Coprinus, Auricularia and Volvariella. Another wild locally growing mushroom with nutraceutical potential is Lentinus tigrinus, which are usually found growing on fallen logs. In our desire to develop a practical production technology for this mushroom, we initiated study on its biophysiology. The secondary mycelia growth and fruiting body performance were elucidated with special reference to the influence of different indigenous culture media, pH, aeration and illumination. The secondary mycelia grew best on coconut water gulaman with a pH of 8 while being incubated in sealed and dark condition. Among the evaluated granular spawn, palay seeds yield very luxuriant mycelia growth having the shortest incubation period of 5 days. Highest biological efficiency of 15.93% was recorded in a formulation consisting of 8 parts of rice straw + 2 parts of sawdust. Lentinus tigrinus has a great potential for cultivation as another newly recorded and propagated Philippine wild edible mushroom.
Keywords: Edible mushrooms